PENGELOLAAN AIR DIKALANGAN PENDUDUK MISKIN DI KOTA SEMARANG: PEMBELAJARAN DARI TINGKAT LOKAL - Laksmi Rachmawati; Gusti Ayu Ketut Surtiari (Jurnal Kependudukan Indonesia, 2011)
Fulfillment of water services for urban poor is still- an issue among academicians and practicioners. Eventhough the Law has stated that access to clean water is the rights of each citizens, there are still numbers of poor people that have no access to clean water. For the urban poor, access to clean water have to be traded off with expensive price. It leads to the household water expenses, reach to more than half of total household expenses. Nowadays, water services from government provider (PDAM) have not reach all possible customers. Limited infrastructure and water sources give impacts to limited services from PDAM This situation also apply for Semarang City case, PDAMTirta Moedal can only reach about .fifty percent of peoples demand For solving the problems, there are some initiatives coming from local people for fulfilling water needs co/ectively such as in Sukorejo and Tugurejo. These two local/eve/ water fulfi/lement systems, showed how the flexibility of local people can help in fulfilling the need of citizen to clean water. This article describes the process of local people developing these initiatives, the mechanism of water fulfillment in each system, impact of the water management in the local level to its accessibility and its sustainability. These initiatives can be used as lesson learned for other areas.Keywords: water services, water fulfillment in local/eve/, poor household, urban areas